2012
DOI: 10.1002/rcm.6310
|View full text |Cite
|
Sign up to set email alerts
|

Identification, quantification and carbon stable isotopes determinations of organic acids in monofloral honeys. A powerful tool for botanical and authenticity control

Abstract: This study has provided a method to differentiate honeys from seven botanical origins, based on organic acid analysis. By combining various organic acid contents and isotopic ratio values through statistical processing by Principal Component Analysis it is possible to differentiate honey samples as a function of their botanical origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The total acid content increases due to the fermentation phenomena and aging that may occur during storage [82]. Some authors have suggested that organic acid profiles are useful for identifying the botanical and/or geographical origin of honey [83].…”
Section: Organic Acids Compositionmentioning
confidence: 99%
“…The total acid content increases due to the fermentation phenomena and aging that may occur during storage [82]. Some authors have suggested that organic acid profiles are useful for identifying the botanical and/or geographical origin of honey [83].…”
Section: Organic Acids Compositionmentioning
confidence: 99%
“…There are also differences in composition of organic acids in the monofloral honey varieties. Therefore, the acids can be used as internal standards in order to detect honey adulteration (Daniele and others ).…”
Section: Carbohydrates and Organic Acids In Foods Of Animal Originmentioning
confidence: 99%
“…There are many means of adulterating honey, including the addition of cheap sugars and syrups after collection of honey from hives (Daniele et al 2012), overfeeding bees with saccharides or invert saccharide derivatives, to increase honey production (Kolayli et al 2012) and the falsification of the floral or geographical origin of the honey (Daniele et al 2012). Honey mislabelling and fraud is a global issue (Moore et al 2012;Fairchild et al 2003).…”
Section: Honey Adulterationmentioning
confidence: 99%